Does The Smart Board Improve Skills Of The First Year Medical Students In Learning Biochemistry? - Krishna Mohan, Surapaneni (INTI University College, 2009)
Biochemistry is one of the basic medical sciences subject introduced in the first year of the medical curriculum. At Saveetha University Medical College Hospital, the approach used in teaching biochemistry is lecture-based strategy by using SMART board. The purpose of this study was to investigate the correlation between use of the SMART board as a teaching- learning methodology in a first year MBBS classroom and student attention to and participation in learning the lessons. Student attention was identified as Looking at the speaker, looking at the smart board, looking at reading material and materials used to present during the learning sessions. This study examines the effect of SMART board on 1g year medical student’s academic performance in Biochemistry. Also this paper examines the ways in which the SMART board technology was integrated into number of areas in 11w curriculum during the year of the medical students at Saveetha Medical College, Saveetha University. The purpose of this study was to investigate teacher’s use and student’s perceptions regarding the SMART board as an instructional tool to teach biochemistry to the medical students. The SMART board is a computerized white board through which new ideas can be recorded, saved, recalled and integrated with the other information because of these special features It was assumed that the SMART board would facilitate interactive and collaborative learning and these effects would be evident In Improved test scores, generation of Ideas and satisfaction of the students with most aspects of the SMART board. Participants were 1’ year MBBS students who were admitted to Saveetha Medical College, Saveetha University during the academic year 2008.09. An intervention group of 75 students used the SMART board to facilitate the active learning process while a comparison group of 75 students, not assigned to a SMART board Intervention, used a conventional method of black board teaching. To diminish the intervention effects between the two groups, the comparison group completed a post-discussion evaluation exercise using SMART board. It was observed that there is a significant Increase In the test scores In the Intervention group as compared to the control group. A 5-point Likert scale questionnaire containing 15 questions was administered to the students to know their perception on the usefulness 01 the SMART board and completed by alt the 150 students of 1g year MBBS. 98% of the students reported improvement in motivation. Alt students thought that the SMART board was effective in terms of learning gains and 98% thought it was essential for their learning outcome to be achieved in learning clinical biochemistry. All of them were enthusiastic about the SMART board and alt were impressed by Instructor’s use in teaching biochemistry.